Correlation between apoptosis, proliferation and bcl-2 expression in malignant non-Hodgkin's lymphoma. Issue 5 (October 1996) - Kiberu, S W; Pringle, J H; Sobolewski, S; Murphy, P; Lauder, I
Abstract : Aim —To investigate whether clinical features of non-Hodgkin's lymphomas, at the time of first biopsy, correlate with studies of cell proliferation and cell death as well as with the level of bcl-2 expression. Methods —Bcl-2 expression, determined by immunocytochemistry, was compared with cell proliferation, measured using in situ hybridisation for histone mRNA, and cell death by apoptosis, measured using in situ end labelling for DNA cleavage. Results —Histone mRNA staining gave a labelling index of 30% of cells for reactive germinal centres, 5.2-13.5% of cells for low grade non-Hodgkin's lymphoma and 12.1-50.5% of cells for high grade non-Hodgkin's lymphoma. In situ end labelling gave a labelling index of 5.0-10.0% of cells for reactive germinal centres, 1.0-3.7% of cells for low grade non-Hodgkin's lymphoma and 4.7-13.5% of cells for high grade non-Hodgkin's lymphoma. There was a positive correlation between apoptotic index and proliferation index. More cases of low grade than high grade non-Hodgkin's lymphoma expressed bcl-2. There was no correlation between apoptotic index and bcl-2 expression for high grade non-Hodgkin's lymphoma. Conclusions —The molecular mechanisms controlling cell proliferation and death in non-Hodgkin's lymphoma are complex, probably involving a range of genes, including bcl -2. A better understanding of resistance to cell death is needed if the clinical goal of tailoring cancer treatment to individual tumours is to be achieved.